POSISI NAṢ DALAM IJTIHAD ‘UMAR IBN KHAṬṬĀB - Jawwas, Fahmi (Hunafa: Jurnal Studia Islamika, 2013)
Abstract. This article discusses the position of the naá¹£ in the ijtihad of â€˜Umar ibn Khaá¹á¹Äb. â€˜Umar is a companion of the Prophet who is known to have insight and intelligence. He is known by Muslims as the father of the mujtahid. Courage in ijtihad sometimes spawned debate among scholars. Some have even considered that aspect of ijtihad put the benefit greater than the naá¹£. This is because the results of ijtihad impressed-for some people-contrary to what is contained in the passage, both the Qur'an and Sunnah. Is it true that â€˜Umar ibn Khaá¹á¹Äb rule out naá¹£ in ijtihad such allegations as scholars? While on the other hand, 'Umar was a man who got recognition by the Prophet over his intelligence in understanding the religion (Islam). This is what will be examined in this paper.Kata kunci: ijtihad, maslahat, naá¹£, fiqh